UJI PERBANDINGAN KOMPOSISI BEBERAPA JENIS LIMBAH PERTANIAN SEBAGAI BAHAN PEMBUATAN KERTAS DAUR ULANG (The Comparison Test of Composition of Several Types of Agricultural Waste as Materials of Recycled Paper) - Sri Indah Lestari; Riswanti Sigalingging; Sulastri Panggabean (Universitas Sumatera Utara, 2018)
ABSTRACT The amount of paper waste produced resulting in problem; one of the ways to overcome it, is by making paper waste as a recycled paper materials. Recycled paper can be made with a mixture of cellulose and hemicellulose from plants.This study aimed to obtain the best composition ofmaterials in recycled paper making by using waste paper and some types of agricultural waste fiber (rice straw, banana leaves, and oil palm leaves).This study was conducted by using a complete non-factorial randomized design. Percentage of ratio of mixture of agricultural waste fiber (rice straw, banana frond,and oil palm leaves) and waste paper were (0%:100%; 25%:75%; 50%:50%; 75%:25%; 0%:100%). Parameters observed were tear resistance, tensile strength, stiffness, roughness, and water absorption.The results showed that the composition of paper waste affected significantly on tear resistance, tensile strength, stiffness, roughness and water absorption. The best paper was obtained on a percentage of 50% of paper pulp and 50% mixtureof agricultural waste fiber with a tear resistance value of 0.72 N.m2/kg, tensile strength of 2.28 k.N/m, paper stiffness 663.00 gf.cm, roughness 2,400 m.L/minute and water absorption 608.0 g/m2.Key words: Recycled paper, art paper, waste of agricultural, pulp, fiber. ABSTRAK Banyaknya sampah kertas yang dihasilkan menimbulkan permasalahan, salah satu cara mengatasinya dengan menjadikan sampah kertas sebagai bahan pembuatan kertas daur ulang. Kertas daur ulang dapat dibuat dengan campuran selulosa dan hemiselulosa dari tanaman. Penelitian ini bertujuan untuk mendapatkan perbandingan komposisi bahan yang paling baik dalam pembuatan kertas daur ulang dengan memanfaatkan kertas bekas dan beberapa jenis serat limbah pertanian (jerami padi, pelepah pisang, dan daun kelapa sawit). Penelitian ini dilakukan menggunakan rancangan acak lengkap non-faktorial. Persentase perbandingan komposisi campuran serat limbah pertanian (jerami padi, pelepah pisang, dan daun kelapa sawit) dan kertas bekas (0% : 100% ; 25% : 75% ; 50% : 50% ; 75% : 25% ; 0% : 100%). Param eter yang diamati yaitu ketahanan sobek, ketahanan tarik, kekakuan, kekasaran, dan daya serap air. Hasil penelitian menunjukkan bahwa komposisi sampah kertas memberikan pengaruh berbeda sangat nyata terhadap ketahanan sobek, ketahanan tarik, kekakuan, kekasaran dan daya serap air. Kertas terbaik didapatkan pada persentase komposisi pulp kertas 50% dan campuran serat limbah pertanian 50% dengan nilai ketahanan sobek 0,72 N.m2/kg, ketahanan tarik 2,28 k.N/m, kekakuan kertas 663,00 gf.cm, kekasaran 2.400 m.L/menit dan daya serap air 608,0 g/m2. Kata Kunci: Kertas daur ulang, kertas seni, limbah pertanian, pulp, serat.